2008
DOI: 10.1152/ajpheart.00027.2008
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in the type II diabetic db/db mouse: impaired venoocclusion with altered cavernosal vasoreactivity and matrix

Abstract: Luttrell IP, Swee M, Starcher B, Parks WC, Chitaley K. Erectile dysfunction in the type II diabetic db/db mouse: impaired venoocclusion with altered cavernosal vasoreactivity and matrix. Am J Physiol Heart Circ Physiol 294: H2204-H2211, 2008. First published March 7, 2008 doi:10.1152/ajpheart.00027.2008.-The number of men with type II diabetes-associated erectile dysfunction (ED) continues to grow rapidly; however, the majority of basic science studies has examined mechanisms of ED in animal models of type I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 23 publications
5
76
2
Order By: Relevance
“…These differences can be ascribed to the more deleterious effect of the elevated plasma glucose levels in established diabetes compared with the mild hypergylcemia found in the prediabetic OZR. On the other hand, dilatations to ACh were more severely impaired in PAs from OZRs than in the corpus cavernosum from db/db mice (30), which is in agreement with that reported for human PAs and the corpus cavernosum from diabetic patients (1). The differential impairment of endothelial function in PAs and the corpus cavernosum may be due to the different contribution of the various endothelial factors, i.e., NO, prostanoids, and EDHF, to the relaxations of penile vascular tissues (1,40).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These differences can be ascribed to the more deleterious effect of the elevated plasma glucose levels in established diabetes compared with the mild hypergylcemia found in the prediabetic OZR. On the other hand, dilatations to ACh were more severely impaired in PAs from OZRs than in the corpus cavernosum from db/db mice (30), which is in agreement with that reported for human PAs and the corpus cavernosum from diabetic patients (1). The differential impairment of endothelial function in PAs and the corpus cavernosum may be due to the different contribution of the various endothelial factors, i.e., NO, prostanoids, and EDHF, to the relaxations of penile vascular tissues (1,40).…”
Section: Discussionmentioning
confidence: 83%
“…This reduction of the smooth muscle content would be consistent with the reduced contractility found in the PAs of OZRs in the present study. On the other hand, a recent study (30) in the type 2 diabetic db/db mouse also reported matrix alterations in the corpora cavernosa consisting of dysregulation of the collagen and elastin content and associated with impaired venoocclusion and reduced erectile responses. Therefore, remodeling of penile tissues, both arterial and corporal, correlates with ED in metabolic syndrome and type 2 diabetes (28,30).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hydroxyproline analyses were performed as previously described (24,25). Conditioned media were collected from serum-starved RPMCs and HPMCs treated with PBS or TGF-b in the presence or absence of uPA and/or RAP at 37 8 C for 48 hours.…”
Section: Hydroxyproline Analysismentioning
confidence: 99%
“…The db/db 2/2 mice lack leptin receptors, and this deficiency contributes to the development of both diabetes and obesity. Therefore, these mice are widely considered an appropriate model for DM2, which has been used for the study of DM2-associated ED (Luttrell et al, 2008). In addition, db/db 2/2 mice develop hyperglycemia and hyperinsulinemia, the latter of which raises resting sympathetic output and contributes to impaired cavernosal relaxation (Anderson et al, 1991).…”
Section: Introductionmentioning
confidence: 99%